Comparative Study of Face-to-Face and Online Teaching Outcomes in Biology - Tana; Tumurkhuu Bayanmunkh; Yadamsuren Oyunchuluun; Dechinperlii Enkhhtuvshin; Chuluunbaatar Enkhbat (Lavai, 2023)
Since the introduction of the Internet in China in 2000, the number of Internet users has consistently grown (TITC, 2010). Amidst the global pandemic, electronic applications have proven advantageous in delivering education. In this study, we designed a progress test involving 60 students who covered the same content in the biology course at the Vocational Education College of China's Ministry of Education and Culture, both through online and inclass formats. There was no significant difference in the overall results for the first semester between students who studied biology online and those in the traditional classroom setting. However, the test scores of online students were found to be slightly lower than those of their counterparts in the classroom. The reliability of the evaluation task developed in this study is deemed good, and improvement is needed, particularly in terms of the discrimination index, which stands at 54.4%. About 32.1% of the tasks were rated as good or very good, with the majority (78.8%) being categorized as relatively easy based on the difficulty index. Based on our research findings, it is plausible to consider conducting biology lessons in the future through online or hybrid courses in addition to traditional classroom settings.